Borel resummation of soft gluon radiation and higher twists - Forte, S; Ridolfi, G; Rojo, J; Ubiali, M (2006)
We show that the well-known divergence of the perturbative expansion of resummed results for processes such as deep-inelastic scattering and Drell-Yan in the soft limit can be treated by Borel resummation. The divergence in the Borel inversion can be removed by the inclusion of suitable higher twist terms. This provides us with an alternative to the standard 'minimal prescription' for the asymptotic summation of the perturbative expansion, and it gives us some handle on the role of higher twist corrections in the soft resummation region. © 2006 Elsevier B.V. All rights reserved.